Compendium of Transgenic Crop Plants 2008
DOI: 10.1002/9781405181099.k0304
|View full text |Cite
|
Sign up to set email alerts
|

Faba Bean

Abstract: Vicia faba L. is an old world grain legume, combine harvested for food and feed in Europe, North and East Africa, Asia, and in the northwest of South America. It is an annual, diploid plant ( x = 6), with a large genome (1C ∼ 13 pg of DNA), large seeds (0.3 up to >2 g per seed), and a protein content of about 30%. Being a small agricultural species, a relatively large producer in Europe is the United Kingdom with more than 150000 ha. On the global scale, Chin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 74 publications
0
9
0
Order By: Relevance
“…Faba bean ( Vicia faba L.) is an important crop in semi-arid regions around the world, but it is considered to be sensitive to moisture stress (Loss et al, 1997a). Escape from terminal drought is used in many semi-arid environments (Loss et al, 1997b; Link et al, 2008), and osmotic adjustment (OA) has not yet been shown (Khan et al, 2010; Duc et al, 2015), but avoidance of transient drought is challenging to investigate because of the range of severities and timings that it can take. Wide variation in shoot and root responses to water deficit has been found at the flowering (Khan et al, 2007; Khazaei et al, 2013a; Khazaei et al, 2013b) and vegetative stages (Belachew et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Faba bean ( Vicia faba L.) is an important crop in semi-arid regions around the world, but it is considered to be sensitive to moisture stress (Loss et al, 1997a). Escape from terminal drought is used in many semi-arid environments (Loss et al, 1997b; Link et al, 2008), and osmotic adjustment (OA) has not yet been shown (Khan et al, 2010; Duc et al, 2015), but avoidance of transient drought is challenging to investigate because of the range of severities and timings that it can take. Wide variation in shoot and root responses to water deficit has been found at the flowering (Khan et al, 2007; Khazaei et al, 2013a; Khazaei et al, 2013b) and vegetative stages (Belachew et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, higher stomatal conductance is positively correlated with higher biomass or yield gain (Blum, 2015; Gosa et al, 2018), as stomatal closure hinders carbon assimilation. Although early closure of stomata is one of the mechanisms by which faba bean deals with drought stress (Link et al, 2008), it often arises from the inability of roots to access moisture from the soil (Blum, 2009; Tuberosa, 2012). Hence, combinations of traits are important to improve the yield of faba bean and other crops for drought-affected areas (Khan et al, 2007; Krishnamurthy et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The second one is Vicia faba equine that has medium seed size. The third, Vicia faba minor, has smaller seed size with round shapes (Link et al, 2008). Each botanical types contains different varieties known by different common names.…”
Section: Ntroductionmentioning
confidence: 99%
“…The presence of stipule spot pigmentation was proposed as an early morphological marker indicating wild-type 'coloured' flowers (tannin-containing faba bean), where there is a black spot on each wing petal and dark vein markings on the standard petal (Picard, 1976). The absence of the pigmentation was considered as the corresponding early morphological indicator for the white-flower, zerotannin trait (Link et al, 2008). ILB 938, however, carries a rare allele (ssp1) that decouples pigmentation in flowers from that in stipules, so it has colourless stipules and coloured flowers (Supplementary Figure S1, Khazaei et al, 2014a).…”
Section: Morphological Markersmentioning
confidence: 99%